ChemInform Abstract: Facile Synthetic Method for Diverse Polyfunctionalized Imidazoles by Means of Pd‐Catalyzed C—H Bond Arylation of N‐Methyl‐4, 5‐dibromoimidazole. Issue 5 (February 2015) - Yamauchi, Takayuki; Shibahara, Fumitoshi; Murai, Toshiaki
Abstract The palladium‐phenanthroline catalyst prefers C‐H bonds over C‐Br bonds in arylation of dibromoimidazole.